2010
DOI: 10.1021/nl102100m
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots Modulate Leukocyte Adhesion and Transmigration Depending on Their Surface Modification

Abstract: Although different nanosized materials, including quantum dots (QDs), are intended to be used for biomedical applications, their interactions with microvessels and their inflammatory potential are largely unknown. In this in vivo study we report that leukocyte recruitment is modulated in the presence of quantum dots. We found that the surface chemistry of QDs strongly affects their localization in postcapillary venules, their uptake by perivascular macrophages, and their potential to modify steps of leukocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 58 publications
9
49
1
Order By: Relevance
“…These cells are able to facilitate the exit of leukocytes from postcapillary venules by rapid degranulation and the release of proinflammatory mediators [40]. Mast cells are not affected by the microsurgical preparation and do not contribute to the low baseline levels of preparationinduced leukocyte recruitment as we and others have reported previously [35,41]. To test whether mast cells are involved in the local recruitment of leukocytes after microinjection of CpG tubes, mice were pretreated with cromolyn, an inhibitor of mast cell degranulation, prior to microinjection.…”
Section: Mast Cell Inhibition Abolishes Cpg Tube-evoked Leukocyte Adhsupporting
confidence: 56%
See 2 more Smart Citations
“…These cells are able to facilitate the exit of leukocytes from postcapillary venules by rapid degranulation and the release of proinflammatory mediators [40]. Mast cells are not affected by the microsurgical preparation and do not contribute to the low baseline levels of preparationinduced leukocyte recruitment as we and others have reported previously [35,41]. To test whether mast cells are involved in the local recruitment of leukocytes after microinjection of CpG tubes, mice were pretreated with cromolyn, an inhibitor of mast cell degranulation, prior to microinjection.…”
Section: Mast Cell Inhibition Abolishes Cpg Tube-evoked Leukocyte Adhsupporting
confidence: 56%
“…It is well documented that the phagocytosis of different nanoparticles by alveolar macrophages is crucial for the production and release of cytokines [50,51], as well as the production of inflammatory mediators in monocytes [52] and macrophages [53]. Moreover, we have previously reported that the surface chemistry of quantum dot nanoparticles determines their uptake by perivascular macrophages as well as their proinflammatory properties upon systemic injection [35,54]. We found in these studies that solely negatively charged quantum dots (with carboxyl-surface modifications) were rapidly taken up by perivascular macrophages upon systemic injection and subsequently elicited leukocyte recruitment in a mast celldependent manner.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Polar NP coatings result in higher opsonization when compared with a neutrally charged surface. For example a coating with PEG largely prevents protein binding and thus renders them invisible for macrophages (Choi et al 2007;Rehberg et al 2010). Although PEG is often used to make the NP inert to biological environment, it doesn't prevent interactions with all biomolecules.…”
Section: The Possible Mechanisms Of Transplacental Transport Of Npmentioning
confidence: 99%
“…However, neutrophil extravasation (i.e., the process of neutrophil interaction with the vessel walls) also participates to the inflammatory response in several pathologies (Chin and Parkos 2007). It is therefore a critical element in the evaluation of biomaterial's biocompatibility in the frame of clinical and/or tissue engineering applications (Rehberg et al 2010). Neutrophils are activated by the local delivery of chemotactic molecules that induce their homing and directional migration toward the sites of infection or inflammation (Nathan 2006).…”
mentioning
confidence: 99%